Utiliser les théories de Bourdieu sur l’École - Alain Garcia (Éducation et Socialisation)
In France, critical sociology developed in the years 1960 with Pierre Bourdieu and Jean-Claude Passeron’s theories. Following the release of Les héritiers and La reproduction, Bourdieu’s theories – with their epistemological basis – have been applied to other work on the school and culture. In this article, I try to describe the tools available for young researchers. Sociological or multidisciplinary research shows the strength of Bourdieu’s paradigm and the ability to adapt its tools (or criticize them). So, Vincent Berry, Marie-Pierre Chopin, Alain Coulon, Christophe Delay, Alain Garcia, Didier Perrier, Ugo Palheta Philippe Perrenoud and Bernard Sarrazy employ the concept of habitus, and they show the importance of practice.